Digital spaces for learning and meeting - A green experiment: Presentation of a blended online-seminar for the Libraries’ network for Ph.D.-support - Grote, Michael; Kavli, Fredrik; Seland, Eli Heldaas (Septentrio Conference Series, 2020)
With climate change and the necessity to reduce travel the public focus on developing online spaces for learning and meeting has strengthened. For this reason we are arranging a blended seminar for the Libraries' network for ph.d.-support: The attendants who are in Bergen or wish to be in Bergen, will meet in a physical conference room, while others will be able to attend the conference as full participants through the online platform Zoom, 29.-30. April 2020. We want to share our experiences with the process of planning and carrying out a blended seminar for this kind of network meetings, and will discuss central issues such as if we succeeded with our ambition to make the seminar accessible for all participants at the same rate, and if the interaction functioned. Did we manage to make interaction and active learning to a main characteristic of the whole meeting? What can be learned from the event, and what could be done better next time? What are important factors to consider when planning to arrange a blended seminar? In line with the green policy of the project we will carry out our presentation online.